Toxicological characteristics of rare earth elements erbium and europium as ingredients of biologically active food additives - Sysa, Aliaksei G. Sysa; telmakh, Victor A.; Vlasenko, Evgenii K.; Yuvs, George V.; Tatyana N., Tatyana N. (Journal of the Belarusian State University. Ecology, 2021)
The toxicological assessment of the rare earth elements erbium and europium is given. It is shown that its salts are moderately and low-toxic compounds, exhibit irritating properties on the mucous membranes of the eyes and damaged skin, and have hepatotoxic and anticoagulant properties. Taking into account scientific data on the toxicity of the components, the “upper permissible level of consumption” of the dietary supplement «YUVS HELP», containing erbium and europium chlorides, was developed − 18 g / person / day, which does not exceed the recommended daily dosage of 8−12 g.
Keywords: erbium; europium; toxicity; dietary supplements; laboratory animals